ANALISIS KESULITAN SISWA DALAM MENULIS PENGALAMAN PRIBADI PADA TEMA KAWAN SEIRING KELAS III SDN 1 SIMPANG TIGA KABUPATEN BENER MERIAH - Khairunnisa Munanto; Intan Safiah; Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the difficulties experienced by elementary school students in writing personal experience texts, particularly in developing ideas and using appropriate language conventions. The purpose of this study was to analyze the level of students’ difficulties and identify the factors influencing these difficulties. This research employed a descriptive qualitative approach with data collection techniques including performance tests, observation, and interviews. The subjects of the study were third-grade students at SDN 1 Simpang Tiga, Bener Meriah Regency. The results showed that students’ writing ability was at a moderate level, with major difficulties found in idea development, completeness of text structure, and the use of spelling and punctuation, while neatness was relatively well achieved. These difficulties were influenced by internal factors such as low motivation, limited vocabulary, and lack of writing practice, as well as external factors including limited instructional time and differences in students’ abilities. In conclusion, improving students’ writing skills requires process-oriented instruction, continuous practice, and intensive guidance. The findings of this study provide practical implications for developing more effective writing instruction at the elementary school level.